Litterfall, litter decomposition, soil macrofauna, and nutrient contents in rubber monoculture and rubber-based agroforestry plantations - Uraiwan Tongkaemkaew; J. Sukkul; Narathorn Sumkhan; Phantip Panklang; Alain Brauman; Roslan Ismail (Forest and Society, 2018)
This study is a comparison of the litterfall, litter decomposition, soil macrofauna, and nutrient contents in rubber monoculture and rubber-based agroforestry plantations. The three intra-couple differences examined are rubber with pakliang (RP) compared with rubber monoculture (RMP), rubber with timber (RT) compared with rubber monoculture (RMT) and rubber with fruit (RF) compared with rubber monoculture (RMF). Rubber plantation systems were selected at 3 plantations located in nearest pairs at 18 plantations in total. Data collected included litterfall at monthly intervals from October 2016 to April 2017, as well as decomposition conditions for assessment at the end of the experimental trials. Soil samples examined the species and number of macrofaunal and decomposition measurements of mesofauna by using Lamina bait scale to analyze nutrient content. Results showed the litterfall of leaves, twinges, and fruits in rubber monoculture and rubber-based agroforestry plantations were not significant between pair comparisons. This showed leaves fell at a high incidence. However, RT experienced a higher trend in litterfall. Decomposing litterfall was also not significant between pair comparisons, but when compared by associated plant species found that RT trends were more likely to experience higher decomposition rates and the litter index was higher as well. Macrofauna in the topsoil (0-5 cm) and subsoil (5-10 cm) were not significant. The composition of mesofauna was found at high decomposition rates in RF, RP, and RT. Organic matter and nutrient contents were not significant in both soil layers. Our data emphasizes that rubber-based agroforestry plantations help regulate C and nutrient cycles, implying that external input fertilizer management requirements for rubber farmers decreased.